An Analysis of Students’ Learning Needs for the Seventh Grade Students at MTs. Barana - Sri Nurnaninsih Ali; Syarifuddin Dollah; La Sunra (PT ARRUS Intelektual Indonesia, 2024)
This research aims to identify the needs of students at Madrasah Tsanawiyah (MTs.) Barana. This research used a qualitative descriptive research design with 10 seventh-grade students as the subjects in this research. In collecting the data, the research instruments in this research were interview guides. The interview was conducted with a student to find out their needs for English lessons. The researcher found that the needs of MTs. Barana students related to English lessons were the need for images in the textbook, vocabulary list to assist students knowing the meaning, more emphasis on pairs learning and learning should more focus on how to read and pronounce the words in English. Additionally, the students also revealed their needs for English lessons. First, the students’ necessities are English as a subject at school thus they need it to pass the exam, go abroad, and achieve their dreams as well as they want to learn English because never learned it in Elementary school. The second, is students’ lack or difficulty, they are difficult to find the meaning, read the passage and pronounce the word in the textbook. The third, students’ wants are images to assist them in guessing the meaning. The fourth, student skills needed are vocabulary, reading and pronunciation. The last, student learning styles are listening or auditory learning and they prefer to learn in pairs compared with individually as well as in groups.